Historical and current landscape‐scale ponderosa pine and mixed conifer forest structure in the Southern Sierra Nevada. Issue 5 (15th May 2015) - Stephens, Scott L.; Lydersen, Jamie M.; Collins, Brandon M.; Fry, Danny L.; Meyer, Marc D.
Abstract : Many managers today are tasked with restoring forests to mitigate the potential for uncharacteristically severe fire. One challenge to this mandate is the lack of large‐scale reference information on forest structure prior to impacts from Euro‐American settlement. We used a robust 1911 historical dataset that covers a large geographic extent (>10, 000 ha) and has unbiased sampling locations to compare past and current forest conditions for ponderosa pine and mixed conifer forests in the southern Sierra Nevada. The 1911 dataset contained records from 18, 052 trees in 378 sampled transects, totaling just over 300 ha in transect area. Forest structure was highly variable in 1911 and shrubs were found in 54% of transects. Total tree basal area ranged from 1 to 60 m 2 ha −1 and tree density from 2 to 170 ha −1 (based on trees >30 cm dbh). K‐means cluster analysis divided transects into four groups: mixed conifer‐high basal area (MC High BA), mixed conifer‐average basal area (MC Ave BA), mixed conifer‐average basal area‐high shrubs (MC Ave BA Shrubs), and ponderosa pine (Pond Pine). The percentage of this 1911 landscape that experienced high severity fire was low and varied from 1–3% in mixed conifer forests and 4–6% in ponderosa pine forests. Comparing forest inventory data from 1911 to the present indicates that current forests have changed drastically, particularly in tree density, canopy cover, the density of large trees, dominance of white fir in mixed conifer forests, and the similarity of tree basal area in contemporary ponderosa pine and mixed conifer forests. Average forest canopy cover increased from 25–49% in mixed conifer forests, and from 12–49% in ponderosa pine forests from 1911 to the present; canopy cover in current forest types is similar but in 1911 mixed conifer forests had twice the canopy cover as ponderosa pine forests. Current forest restoration goals in the southern Sierra Nevada are often skewed toward the higher range of these historical values, which will limit the effectiveness of these treatments if the objective is to produce resilient forest ecosystems into the future.